Micro-assembly technologies and applications : IFIP TC5 WG5.5 Fourth International Precision Assembly Seminar (IPAS'2008) Chamonix, France, February 10-13, 2008 - Ratchev, Svetan (Springer, 2017)
International Federation for Information Processing